Long-Term Safety of JAK Inhibitors in Dermatology: A Literature Review of 2020-2025 - Słomianny, Marcela; Czechowski, Michał; Sikora, Gabriela; Kutnik, Karolina; Kolada, Karolina; Gunia, Katarzyna; Dudek, Filip; Lese, Dominik (Quality in Sport, 2026)
Background. In recent years, Janus kinase (JAK) inhibitors have become an important therapeutic option in dermatology. Agents such as abrocitinib, upadacitinib, baricitinib, deucravacitinib, and ruxolitinibhave significantly changed the management of chronic inflammatory skin diseases, including atopic dermatitis, alopecia areata, psoriasis, and vitiligo. By targeting specific signalling pathways within the JAK–STAT axis, these drugs provide rapid and targeted immunomodulation, offering an alternative to traditional systemic therapies and biologics. However, their long-term safety remains a concern, particularly regarding infections, laboratory abnormalities, dermatologic adverse effects, malignancies, and thromboembolic events. Aim. To summarize the current evidence on the safety profile of JAK inhibitors used in dermatology focusing on data published after 2020. Material and methods. A literature search was conducted in PubMed, Scopus, Frontiers and Cochrane Library databases for studies published between January 2020 and December 2025. Results, JAK inhibitors are effective and generally well tolerated when prescribed with appropriate patient selection and monitoring. The most frequently reported adverse events included infections,laboratory abnormalities, and mild dermatologic reactions, while serious complications such as malignancies or thromboembolic events were uncommon. Conclusion, Evidence from 2020–2025 indicates that JAK inhibitors are effective and generally safe in dermatology. Continued patient monitoring, individualized risk assessment, and further long termstudies are necessary to fully characterize their safety profile.